Is there equity in initial access to formal dementia care in Europe? The Andersen Model applied to the Actifcare cohort. (6th November 2019) - Kerpershoek, Liselot; de Vugt, Marjolein; Wolfs, Claire; Orrell, Martin; Woods, Bob; Jelley, Hannah; Meyer, Gabriele; Bieber, Anja; Stephan, Astrid; Selbæk, Geir; Michelet, Mona; Wimo, Anders; et al.
Abstract : Objectives: In the current study, the Anderson model is used to determine equitable access to dementia care in Europe. Predisposing, enabling, and need variables were investigated to find out whether there is equitable access to dementia‐specific formal care services. Results can identify which specific factors should be a target to improve access. Methods: A total of 451 People with middle‐stage dementia and their informal carers from eight European countries were included. At baseline, there was no use of formal care yet, but people were expected to start using formal care within the next year. Logistic regressions were carried out with one of four clusters of service use as dependent variables (home social care, home personal care, day care, admission). The independent variables (predisposing, enabling, and need variables) were added to the regression in blocks. Results: The most significant predictors for the different care clusters are disease severity, a higher sum of (un)met needs, hours spent on informal care, living alone, age, region of residence, and gender. Conclusion: The Andersen model provided for this cohort the insight that (besides need factors) the predisposing variables region of residence, gender, and age do play a role in finding access to care. In addition, it showed us that the numbers of hours spent on informal care, living alone, needs, and disease severity are also important predictors within the model's framework. Health care professionals should pay attention to these predisposing factors to ensure that they do not become barriers for those in need for care.